Pengaruh Employer Branding dan Pengembangan Karier terhadap Retensi Karyawan melalui Kepuasan Kerja sebagai Variabel Mediasi - Natania Emilia Putri; Widarto Rachbini; Lies Putriana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The increasing intensity of competition among companies compels organizations to retain high-quality employees to sustain performance and competitiveness. Nevertheless, employee retention remains a critical issue influenced by internal factors, including employer branding, career development, and job satisfaction. This study aims to examine the effects of employer branding and career development on employee retention, as well as to analyze their influence on job satisfaction and the mediating role of job satisfaction in these relationships. A quantitative approach was employed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. Data were collected through questionnaires distributed to employees and analyzed using a bootstrapping technique with a significance level of 10% (α = 0.10). The findings reveal that employer branding significantly affects both employee retention and job satisfaction, while career development significantly influences job satisfaction but does not directly impact employee retention. Moreover, job satisfaction significantly affects employee retention and mediates the relationship between career development and employee retention, but not between employer branding and employee retention.